ASSESSMENT TOOLS AND MEASUREMENT OF ELDERLY POPULATION’S WELL BEING IN MODERN PSYCHOLOGY - Abdullayeva Zumrud Chingiz (International Journal of Innovative Technologies in Social Science, 2026)
As is known, the science of psychology studies human behavior; it aims to scientifically determine what human behavior is and what influences it. All observable actions and activities of humans constitute human behavior. Humans are in a constant state of development throughout their lives. As an individual, a person is in a state of physical, mental, emotional, sexual, moral, and social development. These developments encompass the prenatal, infancy, kindergarten, primary school, adolescence, youth, maturity, retirement, old age, and advanced old age stages. The differences in abilities among people in various developmental stages are very large, and learned behavioral patterns are also very different from each other. While studies in the field of psychology worldwide are concentrated on child psychology, educational psychology, organizational psychology, etc., the need for research on geriatric psychology is also coming to the fore. Because the share of the elderly in the world’s population pyramid is increasing. Therefore, new problems are emerging in the physical and mental health of the elderly. The behaviors of the elderly are unique. For this reason, the examination of the psychological state of the elderly should also be on the agenda of those working in psychology. Therefore, this article will attempt to provide an introduction to the psychology of aging and emphasize the importance of the subject.